KONSEP PEMBINAAN AKHLAK PESERTA DIDIK DI SEKOLAH DASAR NEGERI CIBITUNG KULON KABUPATEN BOGOR - Husaeni, Benies; Yuniar, Euis Ismayati; Trikawati (JEDLISH : Journal Of Education and English Language Teaching, 2023)
Morals are traits that are deeply embedded in the human soul, from which traits arise actions and outward movements easily without requiring prior mental consideration. This research is qualitative research taking place at the Cibitung Kulon State Elementary School, Bogor Regency. Data collection was carried out with two types of data in preparing this research, namely, primary data and secondary data. The data collection techniques used in this research are Questionnaire Method, Interview (Interview), and Observation Method (observation and recording). Data analysis in research takes place simultaneously with the data collection process. Among them is through three stages of the water model, namely data reduction, data presentation, and verification. The research results show: (1) Planning for Moral Development by School Principals, Religion Teachers and Class Teachers; (2) The implementation of noble moral development at Cibitung Kulon State Elementary School, Bogor Regency is implemented into a routine program and is carried out on certain occasions/times which are mandatory for students. The exemplary forms shown by the Teachers' Council include discipline in enforcing rules, discipline in behavior, discipline in worship; (3) Output of moral development includes the habit of carrying out prayers on time in congregation, reciting prayers, and respecting, appreciating, and getting used to love and affection towards others, and living a clean life; (4) Supporting factors: a) good cooperation between the principal, teachers, homeroom teacher and all educational staff, b) family factors (parents) who actively participate in giving attention to children to always teach them well and always be a good role model.